Social Influence on Consumer Financial Product Preferences. - Anabo, F. D.
This paper uses conjoint analysis to examine the social influence (e.g., social group recommendations) of an individual consumer?s immediate social circle on his/her financial product preferences. It proposes that social influence from individuals with whom the consumer has strong ties is stronger than that from those with whom he/she has weak ties in choosing financial products through word-of-mouth referral or recommendation. The importance of social influence on financial product preference is associated with consumers? familiarity with the product and their susceptibility to interpersonal influence. Results reveal that recommendations from social groups with strong ties are influential when forming preferences on financial products. Moreover, social influence becomes significant in financial product selection when consumers are less familiar with the product and are more susceptible to interpersonal influence. While this kind of social influence shows a contributory effect, it has a marginal estimated utility compared with the more explicit attributes of financial product choices (e.g., risks and returns). Despite the expected observation, the study shows a tendency to defer to the value of social influence in contexts where consumers are not familiar with a financial product.